"Is the health system ready?" A qualitative exploration of stakeholders' opinions about the feasibility of preconception care services in the Nigerian health system - Oludoyinmola O. Ojifinni; Latifat Ibisomi (BMC, 2022)
Plain Language Summary Optimising the health of women and men in preparation for childbearing can influence pregnancy outcomes positively. This optimisation can be achieved through the provision of preconception care. In many low- and middle-income countries including Nigeria, preconception care is provided in a haphazard manner with no guidelines to structure the service. In this article, the findings from discussions with health care providers and policymakers in Nigeria are presented. These findings show that preconception care can be deployed in a structured manner through collaboration between health care providers and integration with the existing maternal and child health services. Guiding policies can be provided by inclusion of preconception care in the existing health-related policies in the country.